Media and the libel law: The Malaysian experience - Masum, Ahmad; Md Desa, Md Rejab (Elsevier Ltd., 2014)
The media have assumed and reinforced their important role as a legitimate reflection of public interest and opinion.However, the media are peculiarly vulnerable to error of confusing the public interest with their own interest.As a matter of fact, people have increasingly begun to seek the refuge and vindication of litigation.Malaysian media have traditionally focused on nation-building, social cohesion, and “responsible journalism”. This paper aims to examine the operation of libel law on the media in Malaysia. The paper concludes that although there is no mention of press freedom in the Malaysian Federal Constitution, Article 10(1)(a) is assumed to protect press freedom. However, press freedom is not absolute.